[Comment] Brazil-TNT : a randomized phase 2 trial of neoadjuvant chemoradiation followed by FOLFIRINOX versus chemoradiation for stage Ⅱ/Ⅲ rectal cancer - Li Laiyuan; Yang Xiongfei (结直肠肛门外科)
[Background] Neoadjuvant radiation and oxaliplatin-based systemic therapy (total neoadjuvant therapy, TNT) have been shown to increase response and organ-preservation rates in localized rectal cancer. However, trials have been heterogeneous regarding treatment protocols and few have used a watch-and-wait (W&W) approach for complete responders. This trial evaluates if conventional long-term chemoradiation followed by consolidation of FOLFIRINOX increases complete response rates and the number of patients managed by W&W. [Methods] This was a pragmatic randomized phaseⅡ trial conducted in 2 Cancer Centers in Brazil that included patients with T3 or N+ rectal adenocarcinoma. After completing a long-course 54 Gy chemoradiation with capecitabine patients were randomized 1∶1 to 4 cycles of mFOLFIRINOX (Oxaliplatin 85, irinotecan 150, 5-FU 2400)-TNT-arm-or to the control arm, that did not include further neoadjuvant treatment. All patients were re-staged with dedicated pelvic magnetic resonance imaging and sigmoidoscopy 12 weeks after the end of radiation. Patients with a clinical complete response were followed using a W&W protocol. The primary endpoint was complete response: clinical complete response (cCR) or pathological response (pCR). [Results] Between April 2021 and June 2023, 55 patients were randomized to TNT and 53 to the control arm. Tumors were 74% stage 3, median distance from the anal verge was 6 cm, 63% had an at-risk circumferential margin, and 33% an involved sphincter. The rates of cCR + pCR were (31%) for TNT versus (17%) for controls [odds ratio (OR) 2.19, 95% CI 0.8-6.22, P=0.091) and rates of W&W were 16% and 9% (P>0.05). Median follow-up was 8.1 months and recurrence rates were 16% versus 21% for TNT and controls (P>0.05). [Conclusions] TNT with consolidation FOLFIRINOX is feasible and has high response rates, consistent with the current literature for TNT.